The validity and reliability of a new scale to measure patient-determined communication barriers in hospitals - Emine Şahin; Bayram Oğuz Aydın; Murat Taner Gülşen; Seval Kul (Turkish Society of Public Health Specialists, 2017)
Objective: Creating an environment that boosts effective communication between patients and healthcare personnel, and identifying factors that impair good communication, have favorable results on the quality of healthcare services. The primary goal of this study was to develop a new valid and reliable scale that could be used to identify communication barriers at the patient level. Method: The study was conducted with 421 patients receiving healthcare services at Gaziantep University Şahinbey Research and Practice Hospital. The respondents varied in age, gender, education level and by the department to which they were admitted. Descriptive statistics, exploratory factor analysis, confirmatory factor analysis and Cronbach's alpha test were utilized. Results: Based on the analysis of the data collected, a new valid and reliable scale (Cronbach's alpha= 0.81) was constructed, consisting of 28 items and 7 sub-dimensions. Conclusion: The proposed scale showed that the main factors leading to the creation of communication barriers were waiting times, fear and anxiety experienced by the patients, security staff, patients' need for attention, lack of trust towards healthcare personnel, concern and need for being informed and prejudice. Key words: Health communication, communication barriers, patients, healthcare personnel, hospitals